Analysis of Caecal Microbiota in Rats Fed with Genetically Modified Rice by Real-Time Quantitative PCR - Xu, Wentao; Li, Liting; Lu, Jiao; Luo, YunBo; Shang, Ying; Huang, Kunlun (Journal of food science, 2011)
:  The effect of genetically modified rice (GMR) on bacterial communities in caecal content was analyzed in a 90‐d feeding rat model. A total of 12 groups of rats, which included male and female, were fed with the basal diets containing 30%, 50%, 70% GMR (B1, B2, B3) or 30%, 50%, 70% non‐GMR (D1, D2, D3). The structure of intestinal microflora was estimated by real‐time quantitative PCR (RQ‐PCR) based on genus‐specific 16s rDNA primers. SYBR Green was used for accurate detection and quantification of 6 kinds of major bacteria shared by humans and rats. According to RQ‐PCR, the genome copies of Lactobacillus group from the cecum of male rats fed with 70% non‐GMR was higher than those fed with 70% GMR and the relative abundance of Lactobacillus group also higher for group D. This result was in contrast with the E. coli subgroup, which was more numerous in proportion of group B, except D2 and B2 for male rats. The Clostridium perfringens subgroup was numerically more abundant in group D than group B of the same level, also except D2 and B2 for male rats. These results suggested that GMR had a complex effect on caecal microflora that may be related to the health of the host.